Вычислите значение выражения:
а) (2m + 6)n при m = \(-2\frac{1}{2}\), n = 3;
\((2 \cdot -2\frac{1}{2} + 6) \cdot 3 = (2 \cdot -\frac{5}{2} + 6) \cdot 3) = (1 \cdot -\frac{5}{1} + 6) \cdot 3) = (-5 + 6) \cdot 3 = 3\);

б) x - 2xy при x = 5, y = -1;
5 - 2 \(\cdot\) 5 \(\cdot\) (-1) = 5 - 10 \(\cdot\) (-1) = 5 - (-10) = 5 + 10 = 15;

в) ax - 3y при a = 10, x = -5, y = \(-\frac{1}{3}\);
\((10 \cdot (-5)) - (3 \cdot -\frac{1}{3}) = -50 - (-\frac{3}{3}) = -50 + 1 = -49\);

г) ax + bx + c при a = \(\frac{1}{2}\), x = 2, b = -3, c = 5,8;
\((\frac{1}{2} \cdot 2) + ((-3) \cdot 2) + 5,8 = 1 + (-6) + 5,8 = -5 + 5,8 = 0,8\).

Добавить комментарий


Защитный код
Обновить

Возможно, Вам нужно вот это: